Managerial sensemaking in a transforming business ecosystem: Conditioning forces, moderating frames, and strategizing options - Penttilä, Kaisa; Ravald, Annika; Dahl, Johanna; Björk, Peter (Industrial marketing management, 2020)
Disclosing the root cause of managerial action in environments undergoing change, is intrinsically linked to understanding how managers perceive both themselves, and their focal network including the broader surrounding environment. Despite an increased research interest into the interlink between sensemaking and strategizing, empirical evidence on how different limitations manifest in the sensemaking of individual managers in specific contexts is scarce. This study focuses on individual level sensemaking in a transforming business ecosystem as a microfoundation of strategizing. It explores the diverseness of managerial sensemaking by comparing noticed cues, moderating frames and sensemaking outcomes as reflected in different strategizing options. The empirical data derive from 52 semi-structured interviews with top managers in a local business ecosystem. Based on our analysis, we develop an empirically grounded model that unwraps the frames that influence how managers perceive and interpret the changing environment and the implications for their business. Our study provides important empirical corroboration to extant research on the cognitive microfoundations of strategizing in networked environments and adds detail to the underlying sensemaking mechanisms at play. The results highlight the local context and the identity embeddedness of focal actors herein, as factors that significantly influence managerial sensemaking in transforming business ecosystem contexts. •This study explores sensemaking as a microfoundation of strategizing in a transforming business ecosystem.•Findings reveal that managerial perceptions and interpretations are impacted by several moderating frames.•These are technological insight, latitude for strategic change, business model boundaries, and local identity embeddedness.•Our findings help to explain the diverseness of managerial sensemaking in transforming business ecosystems.•Identification of new strategic options seems strongly interlinked with local context and identity embeddedness of focal actors herein.